Reseña. Cognitive linguistic approaches to text and discourse: From poetics to politics. Cristopher Hart (Ed.). Edinburgh University Press, 2019, - Fuica González, Carlos (Arboles y Rizomas, 2022)
Carlos Fuica reseña el libro Cognitive linguistic approaches to text and discourse: From poetics to politics, editado por Cristopher Hart y publicado por Edinburgh University Press en 2019.